Penerapan Restorative Justice di Negara Amerika Serikat - Wahyuningsih, Dewi (Jurnal Ilmiah Penegakan Hukum, 2024)
Restorative justice has been part of the criminal justice system in the United States for more than three decades. Beginning in the 1970s, this approach emerged as an alternative to the retributive nature of the justice system, which tends to focus on punishment as a response to violations of social norms. In contrast, restorative justice places crime victims at the forefront by encouraging dialogue, reconciliation, and the restoration of relationships between offenders, victims, and communities. This approach aims to create a more holistic resolution and reduce the likelihood of reoffending.  This study reviews how Victim Offender Mediation (VOM) serves as one of the main paradigms in the implementation of restorative justice in the United States. VOM allows victims and offenders to engage directly in conflict resolution, resulting in mutually agreeable solutions. In addition, this study compares restorative justice policies in the United States with similar measures in Canada, including the passage of the Youth Criminal Justice Act (2002) which reflects the principles of restorative justice.  The results show that restorative justice has the potential to be a more humane and effective approach in the criminal justice system. However, consistent implementation and a supportive legal framework are needed to ensure its sustainability. This study provides important insights for the development of more inclusive and restorative-oriented criminal justice policies in the United States and other countries.